PERANCANGAN GAME EDUKASI PENGENALAN HEWANDENGAN MEWARNAI BERBASIS ANDROID - Ciko Warisaman, - (2017)
This study aims to produce a medium of introduction of animal learning by way of coloring for children aged 5 years. Currently, interactive multimedia is very necessary for students as a medium of learning. Learning media can use various media means The author's study material in making this final report is about the design of educational game introducing animals and coloring based on android. The development of the game world has penetrated into education in early childhood so as to help the child in developing with the utilization of the world of technology today. With the Android allows users to access education, especially games that contain education. The methodology used is UML (Unified Modeling Language). In this game try to educate the introduction of animals in a way by coloring each image of the animal so that the child can enjoy learning in a way that. By using Android Studio software, Unity 3D, JDK, SDK and Adobe Photoshop cs 6 as a software for designing educational applications of animal recognition by way of coloring